ORGANIZATIONAL AND ECONOMIC MECHANISMS FOR MANAGING TOURISM DEVELOPMENT (Scientific Conference on Multidisciplinary Studies, 2025)
Tourism has become one of the fastest-growing sectors of the global economy, contributing significantly to GDP, employment, and cultural exchange. For developing countries such as Uzbekistan, tourism is not only a driver of economic growth but also a strategic instrument for socio-cultural integration and international cooperation. Effective management of tourism development requires the implementation of robust organizational and economic mechanisms that ensure sustainability, competitiveness and efficiency.